EFEITO DA IDADE RELATIVA NOS CAMPEONATOS ESTADUAIS DE FUTEBOL PROFISSIONAL (Fiep Bulletin - online, 2019)
The objective of this study was to verify if the effect of relative age (EIR) influences the participation of soccer playersin high-performance competitions, in an analysis done in the semi-finalists of the Carioca and Paulista football championships.The birth dates of 689 players were collected. The information was acquired from the register of players published on the websiteof the Federation of Soccer of the state of Rio de Janeiro (www.fferj.com.br) and of the São Paulo Football Federation(www.futebolpaulista.com.br). The birth dates of the players were separated in quarters and the first quarter: born in the monthsJanuary, February and March; 2nd quarter: born in April, May and June; 3rd quarter: born in July, August and September; 4thquarter: born in the months of October, November and December, to be then compared so that it could be concluded if there ispredominance in the choice of players who were born in the first months of the year. The procedure used was descriptive statisticswhere the data were analyzed and the population data profiles were presented. The chi-square test was used to compare thedifferences between quartiles. We adopted a significance level of p